Pengaruh Jus Buah Pepaya (Carica papaya L.) terhadap Profil Farmakokinetik Simetidin pada Tikus Putih (Rattus norvegicus) - Siti Julaicha; Adam M. Ramadhan; Rolan Rusli (Journal of Tropical Pharmacy and Chemistry, 2016)
Drugs used with foods or drinks can affect the drug effects. This study aims to observe the effect of papaya juice (Carica papaya L.) to the pharmacokinetics profile of cimetidine in white rats. The animal were randomly in three group. Group 1 (cimetidine) was given a single oral cimetidine 3,6 mg/200gBW. Group 2 (cimetidine and papaya juice dose I) was given cimetidine 3,6 mg/200gBW together with papaya juice 4,5 g /200gBW. Group 3 (cimetidine and papaya juice dose II) was given cimetidine 3,6 mg/200gBW together with papaya juice 9 g /200gBW. The serial blood was collected for 4 hours on lateralis vein of rats tail. Determination of cimetidine in plasma performed by spectrophotometer UV. The pharmacokinetic parameters of cimetidine were calculated by regresi linear method and recidual method and were analyzed by One Way ANOVA using 95 % confidence interval. Based on research results showed that the group II and group III increased of ka, Cpmaks, tmaks, Cl, AUC and decreased ke, tÂ½ab and tÂ½el. Group III provides the most affect the cimetidine pharmacokinetics profile with decreased absorption and elimination and increased metabolism of cimetidine in rat.